THE ARAL SEA’S ECOLOGICAL, SOCIAL, AND ECONOMIC PROBLEMS - J.A. Ro‘ziev, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The Aral Sea is a large inland water body located in Central Asia and had  significant  ecological  and  economic  importance  until  the  mid-20th  century. However,  the  redirection  of  water  from  the  Amu  Darya  and  Syr  Darya  rivers  to irrigation  systems  caused  the  sea  level  to  drop  sharply,  its  area  to  shrink,  and  an ecological crisis to emerge. This article scientifically analyzes the Aral Sea’s drying, salinization, water quality deterioration, the impact on fisheries and agriculture, as well as  the  social  and  health  problems  for  the  local  population.  In  addition,  ecological restoration and international cooperation measures are discussed, and ways to reduce the  problem  through  rational  management  of  water  resources,  soil,  and  climate monitoring are recommended.